LANGERHANS’ CELL HISTIOCYTOSIS - BOONCHIT, Khomdao; SRINAKARIN, Jiraporn; BOONCHIT, Dumrongsuk; BUNCHALEAW, arinthorn (The ASEAN Journal of Radiology, 2023)
Langerhans’ cell histiocytosis, previously called histiocytosis X is an inappropriate proliferation and infiltration of various tissues with cells that are morphologically and immunologically similar to normal Langerhans cells that is probably due to an immune regulatory defect. We report two different cases of Langerhans’ cell histiocytosis. First case is a 1 year 5 months old girl presented with left eye lid swelling and erythema. Second case is a 2 years old girl presented with multiple skull masses and diabetes insipidus.